2019
DOI: 10.1186/s12885-019-6393-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic consequences of perioperative oral carbohydrates in breast cancer patients — an explorative study

Abstract: Background: The metabolic consequences of preoperative carbohydrate load in breast cancer patients are not known. The present explorative study investigated the systemic and tumor metabolic changes after preoperative per-oral carbohydrate load and their influence on tumor characteristics and survival. Methods: The study setting was on university hospital level with primary and secondary care functions in southwest Norway. Serum and tumor tissue were sampled from a population-based cohort of 60 patients with op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 77 publications
1
10
0
1
Order By: Relevance
“…And the results revealed overexpression of CHAC1 significantly inhibited cell proliferation and induced cell death, but cast limited influence on the abilities of cell migration and invasion. It is reported dysregulated GSH metabolism widely exist in malignant tumours 28‐30 . And Heike Miess has demonstrated that higher levels of GSH were detected in higher malignancy and later stage of KIRC 10 .…”
Section: Discussionmentioning
confidence: 99%
“…And the results revealed overexpression of CHAC1 significantly inhibited cell proliferation and induced cell death, but cast limited influence on the abilities of cell migration and invasion. It is reported dysregulated GSH metabolism widely exist in malignant tumours 28‐30 . And Heike Miess has demonstrated that higher levels of GSH were detected in higher malignancy and later stage of KIRC 10 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective long-term breast cancer study found that perioperative high intake of glucose was not only associated with high insulin blood levels but also with an extremely poor prognosis ( 34 ). This finding could be further correlated with significant metabolomics changes in the blood shortly after the operation ( 35 ). A prospective glucose intervention study, or intervention with medicines which can reduce insulin blood levels in stage IV NSCLC patients, therefore would be interesting.…”
Section: Discussionmentioning
confidence: 78%
“…Some have hypothesized that growth factor stimulation in response to intraoperative tissue damage, can increase HER2 receptor activation in incompletely resected pre-invasive breast cancer thus increasing risk for tumor cell proliferation and spread (141). Procedures that might elevate blood glucose or insulin levels should be avoided, as glucose is known to accelerate breast cancer development (142)(143)(144)(145)(146)(147). Products used in anesthesia might also increase blood glucose and insulin levels (148).…”
Section: Current Standard Of Care (Soc) For Breast Cancermentioning
confidence: 99%
“…KMT should decrease the need for dexamethasone pretreatment, a problematic therapy that can inadvertently increase availability of glucose to the tumor cells while also inhibiting chemotherapyinduced apoptosis (192)(193)(194). It is well-known that glucose and hyperglycemia contribute to rapid breast cancer growth (146,195,196). Consequently, KMT could reduce inflammation and glucose systemically, thus enhancing the anti-tumorigenic properties of the microenvironment.…”
Section: Ketogenic Metabolic Therapymentioning
confidence: 99%